BIOFILM-FORMING MECHANISMS IN DIABETIC FOOT SYNDROME PATHOGENS: ADHESIVE PROPERTIES AND INTERACTION IN ASSOCIATIONS - Yuliia V. Ivanova; Svitlana M. Gramatiuk; Igor A. Kryvoruchko; Mykola M. Goloborodko; Kyrylo V. Miasoiedov; Mykhailo V. Knyhin; Vitalii S. Strakhovetskyi (Клінічна та профілактична медицина, 2025)
Aim. To investigate the adhesive properties and biofilm-forming ability of diabetic foot syndrome pathogens, both individually and in associations, and to compare them with reference strains.